2021
DOI: 10.3390/foods10081943
|View full text |Cite
|
Sign up to set email alerts
|

Selected Quality Parameters of Air-Dried Apples Pretreated by High Pressure, Ultrasounds and Pulsed Electric Field—A Comparison Study

Abstract: The aim of this work was to compare selected physicochemical properties of air dried ‘Golden Delicious’ apples, pretreated either by high-pressure processing (HPP), ultrasound (US) or pulsed electric field (PEF). Following parameters of pretreatment were used: HPP–400 MPa for 15 min, US–21 kHz, 180 W for 45 min, PEF–1 kV/cm, 3.5 kJ/kg. The quality of materials was evaluated by their rehydration properties, hygroscopicity, color and total phenolic content. To compare the effectiveness of the utilized methods, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
2
7
0
1
Order By: Relevance
“…22 This phenomenon facilitates the removal of pesticide residues and other contaminants present on the surface of the peel, while causing minimal or negligible changes in the internal cellular structure where polyphenols are located, slowing down their removal, consistent with the findings of Wiktor et al (2021). 46 On the other hand, when PEF was applied to potato peel samples, short intense electric pulses were employed causing electroporation of the internal cell membranes. 47 This electroporation phenomena could lead to the formation of temporary pores in the cell walls, allowing for the release of intracellular compounds, including phenolic compounds and other bioactive substances.…”
Section: Resultsmentioning
confidence: 99%
“…22 This phenomenon facilitates the removal of pesticide residues and other contaminants present on the surface of the peel, while causing minimal or negligible changes in the internal cellular structure where polyphenols are located, slowing down their removal, consistent with the findings of Wiktor et al (2021). 46 On the other hand, when PEF was applied to potato peel samples, short intense electric pulses were employed causing electroporation of the internal cell membranes. 47 This electroporation phenomena could lead to the formation of temporary pores in the cell walls, allowing for the release of intracellular compounds, including phenolic compounds and other bioactive substances.…”
Section: Resultsmentioning
confidence: 99%
“…Then the fruits were kept in the refrigerator at 4 to 6 °C to prevent rotting. Samples were placed at ambient temperature for 2 h before the tests 22 . The apples were washed and peeled then cut into slices of 2, 4, and 6 mm thickness with a knife.…”
Section: Methodsmentioning
confidence: 99%
“…In food processing, ultrasound causes changes in textural, rheological, physical, chemical and functional properties 19 . Several studies have also dried various food products using ultrasound pretreatment for Inula viscosa (L.) 17 , pumpkin seeds 20 , longan 21 , apple 22 , celery 23 , carrot 24 , and kiwifruit 25 . The results showed that pretreatments with different drying methods can be applied to decrease and increase the DT and the efficiency, respectively while preserving the final sample quality.…”
Section: Introductionmentioning
confidence: 99%
“…These additives are known to be prejudicial to human health, and are associated with a variety of health problems. This collection includes four reviews and six original research articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The review on high-pressure processing (HPP) technology is focused on fruit and vegetable products [ 1 ].…”
mentioning
confidence: 99%
“…The review showed minimal impact of pulsed electric fields (PEF), HPP and ultrasound on the quality of the wine [ 4 ]. A comparative study of the application of HPP, ultrasound and PEF for the pre-treatment of apples before air drying is included in this collection [ 5 ].…”
mentioning
confidence: 99%